Coping style at diagnosis and its association with subsequent health-related quality of life in women with breast cancer: A 3-year follow-up study. (April 2020) - Cho, Young Up; Lee, Bo Gyeong; Kim, Soo Hyun
Abstract: Purpose: The aim of this study was to describe distinct coping styles of women newly diagnosed with breast cancer and to determine whether there is an association between those styles and the women's long-term health-related quality of life (HRQOL). Methods: Using a prospective longitudinal study design, we enrolled 101 women recently diagnosed with breast cancer in South Korea and asked them to complete a questionnaire that included the Mini-Mental Adjustment to Cancer (Mini-MAC) scale and the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Core 30 (EORTC QLQ-C30). Results: From the baseline data, we identified two coping style clusters. The first ("FS cluster") had higher scores on the fighting spirit subscale and lower scores on the helpless-hopeless and anxious preoccupation subscales (n = 52, 51.5%), while the second ("HHAP cluster") scored higher on the helpless-hopeless and anxious preoccupation subscales and lower on the fighting spirit subscale (n = 49, 48.5%). In the longitudinal analysis, the FS cluster had a better HRQOL then the HHAP cluster for 2 years after diagnosis, but the HRQOLs did not differ significantly 3 years after diagnosis. Conclusions: Maladaptive coping at diagnosis may predict poor HRQOL in women with breast cancer. Regular screening of coping style and interventions to improve poor coping style should be considered for at least 2 years post initial diagnosis. Highlights: Using cluster analysis, we generated two coping style clusters of newly diagnosed women with breast cancer. Maladaptive coping style predicts poor HRQOL for 2 years post-diagnosis. Early screening and intervention for women who reveal maladaptive coping style are critical for optimal HRQOL.